Respuesta :

Answer:

  q = 0

Step-by-step explanation:

We can substitute for x in the given equation, then solve for q.

Substitution

  3x -4 = x +q . . . . . . given equation

  3(2) -4 = 2 +q . . . . using 2 for x

  6 -4 = 2 +q . . . . . eliminate parentheses

  2 = 2 +q . . . . . . . simplify

Solution

Subtracting 2 from both sides of the equation gives the value of q.

  2 -2 = 2 -2 +q . . . . subtract 2

  0 = q . . . . . . . . . . . . simplify

If x=2, the value of q in the equation is zero (0).

ACCESS MORE